PENANAMAN NILAI RELIGIUS DAN KEDISIPLINAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SD NEGERI 2 KALIPUCANGKULON - Mustofa, M. (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
The purpose of this research is to describe the implementation of religious values in student discipline in increasing learning achievement. Religious values have a crucial role in the application of student discipline. Student discipline affects learning activities which can ultimately improve learning achievement. The emphasis in this study is religious values, discipline and student achievement.This type of research is descriptive qualitative. Data obtained through interviews, observation and documentation studies at SD Negeri 2 Kalipucangkulon, Welahan District, Jepara Regency. The research subjects were school principals, class teachers, PJOK teachers, religion teachers, parents/guardians of students and student representatives.The results of the study provide religious values that are instilled in Kalipucangkulon 2 Public Elementary School, Welahan District, Jepara Regency including the values of discipline, responsibility, honesty, tolerance, sincerity, mutual respect and care for the environment. The inculcation of religious values is integrated into the school culture as well as all subjects that influence the learning achievement of SD Negeri 2 Kalipucangkulon students. This study also provides constraints that include internal and external factors on the inculcation of religious values that influence discipline to increase academic achievement.